The Role of Family Awareness in Reducing Information Crimes: A Descriptive Analytical Study on A Sample of Saudi families in Al-Qunfudhah Governorate (The International Journal of Educational Sciences and Arts, 2026)
The study aimed to identify the role of family awareness in reducing information crimes from the point of view of a sample of Saudi families in Al-Qunfudhah Governorate, as well as identifying the forms of information crimes, and their most important risks, and determining the role of the family in developing awareness among its members of information crimes, and knowing the societal obstacles that limit Developing family awareness of information crimes, and the study relied on the social survey approach as an appropriate method for the study. The results of the study are that the most important form of information crime from the point of view of Saudi families in Al-Qunfudhah is the robbery of bank credit cards with a rate of (68%), and that the most important risk of information crime is exploitation and extortion of the victim to obtain her money with a rate of (90.7%), and that the most important role of the family is in developing awareness Its members have awareness of information crimes within the family by dealing with caution with internet and social networking sites by (98%). 88.3%. The study recommended the need to train Saudi family members to take the necessary security measures, procedures, and precautions to protect themselves and their families from information crimes and reduce their risks, which may be due to poor family awareness of these crimes.
Keywords: Family Awareness; Information Crimes; Saudi Families